2020
DOI: 10.3390/genes11091066
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals a Gene Expression Pattern Associated with Fuzz Fiber Initiation Induced by High Temperature in Gossypium barbadense

Abstract: Gossypium barbadense is an important source of natural textile fibers, as is Gossypium hirsutum. Cotton fiber development is often affected by various environmental factors, such as abnormal temperature. However, little is known about the underlying mechanisms of temperature regulating the fuzz fiber initiation. In this study, we reveal that high temperatures (HT) accelerate fiber development, improve fiber quality, and induced fuzz initiation of a thermo-sensitive G. barbadense variety L7009. It was proved th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…The gain or loss of key motifs as species evolved may have resulted in changes to protein functions that altered plant development. Phytohormones and abiotic stresses might affect fiber development through signal transduction pathways (Chen et al 2019;He et al 2019;Cheng et al 2020;Wang et al 2020a, b;Zhang et al 2020;Tian and Zhang 2021;Wu et al 2021). We identified numerous cisacting elements responsive to light, phytohormones, defense processes, and stress as well as multiple TF-binding sites upstream of transcriptional start sites.…”
Section: Discussionmentioning
confidence: 81%
“…The gain or loss of key motifs as species evolved may have resulted in changes to protein functions that altered plant development. Phytohormones and abiotic stresses might affect fiber development through signal transduction pathways (Chen et al 2019;He et al 2019;Cheng et al 2020;Wang et al 2020a, b;Zhang et al 2020;Tian and Zhang 2021;Wu et al 2021). We identified numerous cisacting elements responsive to light, phytohormones, defense processes, and stress as well as multiple TF-binding sites upstream of transcriptional start sites.…”
Section: Discussionmentioning
confidence: 81%
“…MDA, an indicator of lipid peroxidation, was measured according to the manufacturer′s protocol of the assay kit. Antioxidant enzymes, such as SOD and POD, play a critical role in maintaining the balance of the intracellular ROS state, and thus, they were analyzed by the Nitrotetrazolium Blue chloride method and the Guaiacol method for SOD and POD, respectively . The main photosynthetic pigments, including chlorophylls (Chl a and Chl b ) and carotenoids, were determined according to a previous study .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the degree to which temperature can affect Cd accumulation depends on the chemistry of the root zone, plant growth, and biomass ( Fritioff et al., 2005 ; Peer et al, 2005 ). Root immobilization can elucidate substantial amounts of accumulated metals in plants and is affected by temperature, which can modify the structure and function of cell walls by inducing the synthesis of plant hormones ( Liu et al., 2019 ; Cheng et al., 2020 ). In line with this, we found that the root-to-shoot TFs of Cd under T2 (27°C) were generally higher than those under T1 (23°C).…”
Section: Discussionmentioning
confidence: 99%